DETERMINANTS THAT PREDISPOSE TO CONVERSION OF LAPAROSCOPIC CHOLECYSTECTOMY TO OPEN CHOLECYSTECTOMY IN A TERTIARY HEALTH-CARE CENTER IN INDIA - TR, Karthikhaeyan; Visagan, Keerthi; A, Vasantha Ragavan; Sharma, Ankit Kumar; V, Rajasenthil (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The aim of this study was to analyze the patient and disease-related factors of gallstone disease and also to identify pre-operative clinical, laboratory, and ultrasonic predictors that predispose to conversion of laparoscopic to open cholecystectomy. Methods: The study was prospectively conducted over 1-year duration in a tertiary care center in India. Demographic, hematological, and radiological data were recorded for all participants and compared to assess predictors of conversion from laparoscopic to open cholecystectomy. Results: A total of 526 patients participated in the study. Thirty-two cases were converted to open with 6.08% conversion rate. The common intraoperative causes of conversion were frozen Calot’s triangle, dense adhesions, and empyema gallbladder. The significant predictors of conversion were found to be a previous episode of acute cholecystitis (p=0.003), previous upper abdominal surgery (p=0.001), total leukocyte count (p=0.012) with neutrophils (p=0.005), gallbladder wall thickness >5 mm (p=0.0082), and presence of pericholecystic fluid (p=0.0184). Conclusion: The above-mentioned determinants can be used to predict the chances of conversion in a patient planned for laparoscopic cholecystectomy so that the patient can be counseled regarding the risk of conversion and informed consent can be obtained, and the surgical team can be adequately prepared.